Bioinformatic analyses reveal lysosomal-associated protein transmembrane 5 as a potential therapeutic target in lipotoxicity-induced injury in diabetic kidney disease - Xin Chen; Shenglong Zhu; Ciyou Huang; Jiayi Liu; Jinbang Wang; Siyuan Cui (Renal Failure)
Emerging data have revealed that damage to tubular epithelial cell is a driving force in the progression of diabetic kidney disease (DKD). However, the specific mechanisms by which lipotoxicity contributes to the injury of these cells, thereby influencing the development of DKD, are yet to be fully understood. Here, we analyzed the GSE 30529 microarray datasets of human tubulointerstitial tissue samples from the Gene Expression Omnibus database (GEO). Concurrently, we conducted RNA-sequencing on palmitic acid (PA)-treated human renal proximal tubule epithelial cells (HK2 cells). After normalization, the differentially expressed genes (DEGs) were screened by R software and gene ontology (GO) enrichment analysis was conducted, and lysosomal-associated protein transmembrane 5 (LAPTM5) was finally selected. Our findings indicate that the expression of LAPTM5 was obviously increased in DKD patients, and the correlation between LAPTM5, and other clinical parameters of DKD was analyzed using the Spearman correlation analysis. The potential of LAPTM5 as a prognostic biomarker for DKD was further consolidated through receiver operating characteristic (ROC) analysis. To further verify the function of LAPTM5, we established mouse or in vitro systems mimicking DKD. The results showed that a consistent upregulation of LAPTM5, which was also found to be linked with inflammatory mediators within the context of DKD. Additionally, LAPTM5 silencing significantly downregulated mRNA expression of inflammatory factors in PA-treated HK2 cells. These results indicate that LAPTM5 is a potential biomarker and therapeutic treatment target for DKD. This discovery paves the way for future research and development of targeted interventions aimed at mitigating the progression of this prevalent condition.